Wadsworth-emmons reaction by using the fluorapatite catalyst: kinetic studies - Vishwakarma, Rakhi; Vinod, Chathakudath P.; Rathod, Virendra; Kantam, Mannepalli Lakshmi (Industrial & Engineering Chemistry Research, 2023)
Wadsworth-Emmons reaction was successfully carriedout byusing the fluorapatite (FAP) catalyst. The reaction of 2-methoxybenzaldehydeand triethylphosphonoacetate using FAP afforded & alpha;,& beta;-unsaturatedester with 100% conversion and 80% selectivity. A kinetic model wasvalidated at different temperatures by Langmuir-Hinshelwood-Hougen-Watson(LHHW), and the absence of mass transfer resistance was verified bythe Weisz Prater criterion. The effect of different catalysts, temperature,catalyst loading, solvent, mole ratio, and speed of stirring was studied.The FAP catalyst was characterized by Fourier transform infrared spectroscopy,Brunauer-Emmett-Teller method, nitrogen adsorption-desorption,transmission electron microscopy, energy-dispersive X-ray spectroscopy,temperature programmed desorption (TPD-NH3), X-ray diffraction,and X-ray photoelectron spectroscopy. The FAP catalyst was found tobe stable up to three recycles with no loss in activity.

Wurtzite CuGaS2 with an in-situ-formed CuO layer photocatalyzes CO2 conversion to ethylene with high selectivity - Chakraborty, Subhajit; Das, Risov; Riyaz, Mohd; Das, Kousik; Singh, Ashutosh Kumar; Bagchi, Debabrata; Vinod, Chathakudath P.; Peter, Sebastian C. (Angewandte chemie-international edition, 2023)
We present surface reconstruction-induced C-C coupling whereby CO2 is converted into ethylene. The wurtzite phase of CuGaS2. undergoes in situ surface reconstruction, leading to the formation of a thin CuO layer over the pristine catalyst, which facilitates selective conversion of CO2 to ethylene (C2H4). Upon illumination, the catalyst efficiently converts CO2 to C2H4 with 75.1 % selectivity (92.7 % selectivity in terms of R-electron) and a 20.6 mu mol g(-1) h(-1) evolution rate. Subsequent spectroscopic and microscopic studies supported by theoretical analysis revealed operando-generated Cu2+, with the assistance of existing Cu+, functioning as an anchor for the generated *CO and thereby facilitating C-C coupling. This study demonstrates strain-induced in situ surface reconstruction leading to heterojunction formation, which finetunes the oxidation state of Cu and modulates the CO2 reduction reaction pathway to selective formation of ethylene.
Keywords: C-C coupling; charge polarization; CO2 reduction; Photocatalysis

W/HAP catalyzed terpenic alcohols oxidation: kinetic studies - Poman, Aishwarya; Kamble, Paresh; Vinod, Chathakudath P.; Rathod, Virendra; Kantam, Mannepalli Lakshmi (Reaction Chemistry & Engineering, 2025)
The selective oxidation of natural alcohols into carbonyl derivatives is a pivotal transformation in synthetic organic chemistry and industrial applications. This study focuses on the oxidation of borneol, a bicyclic secondary terpenic alcohol, into camphor using a tungsten-exchanged hydroxyapatite (W/HAP) catalyst and hydrogen peroxide as a green oxidant. Hydroxyapatite was synthesized via co-precipitation and functionalized with sodium tungstate to create the W/HAP catalyst, which was characterized using techniques such as SEM, EDS, TPD, XPS, and N2 adsorption-desorption to evaluate its surface morphology, porosity, and chemical composition. Oxidation reactions were conducted under optimized conditions, employing dimethylacetamide (DMA) as a solvent to achieve maximum conversion and selectivity. The W/HAP catalyst demonstrated superior performance, achieving nearly 99% conversion of borneol with 100% selectivity for camphor. Reaction parameters, including temperature, reactant stoichiometry, solvent choice, and catalyst loading, were systematically investigated. Higher reaction temperatures and oxidant concentrations favoured rapid conversion while maintaining high selectivity. Solvent effects revealed that DMA stabilized peroxo-tungstate intermediates, enhancing reaction efficiency compared to other solvents. Kinetic studies confirmed a first-order reaction mechanism with respect to borneol, and the activation energy was determined to be 44.23 kJ mol-1, highlighting the catalytic efficiency of W/HAP. Reusability tests confirmed the stability of the W/HAP catalyst over multiple cycles with minimal tungsten leaching. The methodology was extended to other terpenic alcohols, with varying degrees of success, emphasizing the substrate-specific activity of the catalyst. This work underscores the potential of tungsten-based heterogeneous catalysts in sustainable alcohol oxidation and highlights the industrial relevance of camphor synthesis as a renewable and eco-friendly approach to produce fine chemicals, fragrances, and pharmaceuticals.